FINANCIAL STABILITY MODEL THROUGH EFFICIENCY, PROFITABILITY AND FINANCIAL TECHNOLOGY - Asbi Amin; Buyung Romadhoni; Wahyuni Wahyuni (ZILLZELL MEDIA PRIMA, 2025)
The economy sharia development shows the financial stability of Sharia Bank in ASEAN is increasing. The stable financial condition of banks will have an impact of the balance financial system. This research aims to examine the influence of efficiency, profitability, and financial technology on the financial stability of Islamic banking in ASEAN using Vector Auto Regressive (VAR). This VAR model is a system of simultaneous equations where the number of equations formed is the number of variables used. Each equation is related both mathematically and theoretically. This research uses quantitative method. The population used in this research comes from all sharia banks in the Southeast Asia region which have been operating since 2019 – 2023. This research uses a purposive sampling method where the sample is taken randomly by determining several criteria in the sample. Based on the criteria mentioned above by reviewing certain conditions there are 19 sharia banks that can be used as samples in this research. The research result of the cointegration test indicate that between three variables in this research there is a cointegration correlation at the Significance level of 5%. This means that movements in efficiency, profitability, financial technology, and financial stability have a correlation of stability/balance and similar movements in the long term. Furthermore, the result of the Granger causality test shows that the financial stability and efficiency have a one-way relationship. The p-value of financial stability is 0.042 or < 0.005, namely a one-way relationship; the p-value of profitability is 0,029 or <0,05 which means a reject H0 namely a one-way, and the p-value of profitability is 0,029 or <0,05 which means profitability influence financial stability with a one-way relationship; meanwhile the p-value financial technology is 0,027 or <0,05 which means that financial technology influences financial stability in one-way relationship.